Aplikasi Monitoring Aset Berbasis QR Code Dengan Rule-Based Alert Engine Sebagai Peringatan Dini - Gitarosalina Sibarani; Kristofel Santa; Medi Hermanto Tinambunan (JURIKOM (Jurnal Riset Komputer), 2026)
Asset management at PT PLN Nusantara Power Unit Pembangkitan Minahasa is still carried out manually, which has the potential to cause recording errors and delays in data updates. In addition, most QR Code-based asset management systems that have been developed generally only focus on the process of recording and identifying assets, without being equipped with an early warning mechanism. This study aims to develop a web-based asset monitoring application that integrates QR Code technology with a rule-based alert engine using the Extreme Programming (XP) method. The research methods include iterative software development, functional testing using black box testing, system response time analysis, and user satisfaction evaluation through questionnaires. Testing results show that all system functions run according to user requirements with an average response time of less than 5 seconds, thus supporting real-time use. The rule-based alert engine is capable of automatically detecting asset conditions that require attention and generating notifications as a form of early warning. User evaluation shows a high level of satisfaction with the ease of use and functionality of the system. Based on these results, the developed application has been proven to improve the accuracy of recording and efficiency of asset management compared to manual methods, and has the potential to become an adaptive digital solution in office asset management.